Factor structure, measurement invariance, and construct validity of MELQO measure of child development and early learning in Laos. Issue 2 (3rd April 2022) - Gomez, John A.; Brown, Joshua L.; Spier, Elizabeth
ABSTRACT: Early learning interventions are widely implemented in developing countries yet instruments to reliably measure the effects of such programs on children's development and learning in specific contexts are needed. This study examines the measurement properties of a globally-informed instrument adapted to measure school readiness in Laotian children from ethnolinguistic minorities. Data come from a subsample of children (n = 1469, mean age = 4.67 years) in two larger studies to promote children's school readiness in rural areas in Laos. This study (a) uses exploratory and confirmatory factor analysis to evaluate the factor structure of the measure, (b) tests measurement invariance across ethnolinguistic and age groups, and c) examines the construct validity using demographic variables known to predict school readiness. Results indicate eight factors compatible with subtasks in the Numeracy, Executive Function, and Vocabulary domains, but not with a Literacy domain, and it is useful for making inferences regarding school readiness from children across ethnolinguistic and age groups. Family SES, parents' education, child gender, and age were associated with several domains of children's school readiness. Results are discussed with respect to the importance of assessing children in their first language to help reduce the ethnolinguistic disparity in children's school readiness performance.